FRI0308 Reducing gender disparities in willingness to consider total knee replacement (TKR): The impact of a brief educational intervention. (23rd January 2014) - Volkmann, E.; David, A.; Fitzgerald, J.
Abstract : Background: Studies suggest patients' willingness to consider TKR for osteoarthritis (OA) varies by gender and that women who undergo TKR have more severe OA and greater functional disability than men at the time of surgery. 1 Objectives: To evaluate perceptions of TKR among men and women with knee osteoarthritis and to examine the impact of an educational intervention on changes in expectations of health outcomes following TKR. Methods: Patients with moderate to severe knee OA viewed a video about knee OA treatments and subsequently participated in gender-segregated focus groups addressing patients' questions and concerns regarding TKR. Patients completed baseline and post-intervention questionnaires, which included an adapted Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) to assess post-TKR expectations (0-100 scale with higher scores reflecting worse outcomes). Results: At baseline, women (N=78) had poorer post-TKR expectations about pain compared with men (N=58) (26.4 vs. 18.2, respectively, p=0.28). Following the intervention, women's post-TKR pain expectations fell to levels comparable to male responders (Pre: 26.4 vs. Post: 18.2, p=0.005); whereas men had no significant change in their expectations scores. Women were also more willing to consider TKR after the intervention (Pre: 2.4 vs Post: 3.1, on a 1-5 Likert scale with higher scores reflecting greater willingness; p =0.020), while men had no significant change in their willingness to consider TKR after the video (Pre: 2.4 vs. Post: 2.6). In focus groups, women discussed risks of TKR more frequently than did men. Women also raised the issue that the risks may outweigh the benefits of TKR; whereas men did not raise this concern. In bivariate analysis of all patients, lower WOMAC post-operative expectation pain scores were correlated with an increased willingness to consider surgery ( r =-0.21, p =0.017). Increased risk taking behavior was also associated with increased willingness to consider surgery ( r =0.35, p <0.001). In a logistic regression analysis controlling for age, gender and greater risk taking behavior, better WOMAC expected pain scores remained significantly correlated with willingness to consider surgery (OR 1.52, p =0.003). Conclusions: Perceived post-TKR pain outcomes were independently associated with willingness to consider surgery. Improving patient knowledge of TKR through an educational intervention may help reduce gender disparities in expectations of and willingness to consider TKR. References: Parsley BS, Bertolusso R, Harrington M, et al. Influence of gender on age of treatment with TKA and functional outcome. Clin Orthop Relat Res 2010;468:1759-64. Disclosure of Interest: None Declared